Development a series ignition circuit for simmer operation of Nd: YAG flashlamp driver - Mat Daud, Yaacob (Faculty of Science, University Teknologi Malaysia, 2007)

(untitled)
This present paper describes the development of a series ignition circuit for flashlamp driver. A high voltage ignition pulse produced in series with dc simmer power supply. The ignition is based on a single stage of step-up circuit. A small step up transformer was employed together with scr thyristor as a switch to generate high voltage pulse. In this development, ignition circuit was successfully demonstrated the production of giant pulse of 12 kv with duration of less than 1 µs by injecting only 180 v dc. The pulse is enough to ignite and sustains flashlamp in simmer operation